Does AI Sentiment Affect Stock Returns? Evidence from Indonesia’s Banking Sector - Junanta, Geryan; Rokhim, Rofikoh (Quantitative Economics and Management Studies, 2025)
This study investigates the heterogeneous effects of AI-related investor sentiment on the stock returns of Indonesian banks. Using a correlation-weighted AI Sentiment Index (AI-SVI) derived from Google Trends, panel regressions reveal that only fintech-driven banks show significant responsiveness to AI sentiment, while conventional, independent digital, and conglomerate-backed banks do not. These findings are supported by a supplementary investor perception survey, which confirms that market participants associate visible and strategic AI adoption primarily with fintech institutions. The results suggest that AI sentiment can act as a behavioral signal of valuation in emerging financial markets, but its effectiveness depends on how innovation is perceived and communicated. Policymakers and investors should be cautious in interpreting sentiment-driven movements, especially in sectors with uneven technological maturity.